Seed yield and quality of soybean fields infested by Euschistus heros sublethally exposed to imidacloprid - Bernardo, Ana Maria Guimarães (2019)
Neotropical brown stink bugs, Euschistus heros, 1s the most present pest in Brazilian soybean crop fields. Chemical pesticides are used to reduce this pest on soybean crops such as neonicotinoids. However, some studies reported that, under controlled conditions, these stink bugs demonstrated higher reproduction when exposed to sublethal doses of imidacloprid (neonicotinoid). Thus, the soybean seeds physiological may decrease with these higher E. heros population. Though, plant defence sytem can be induced by herbivores to defend themselves against this pest. Thus, we aimed to known the effects of exposure to imidacloprid sublethal dose on E. heros population under field conditions and possible consequences of such exposure on yield, physiological quality and antioxidant enzymes activity of soybean seeds. Additionally, we investigated whether E. heros exposed to imidacloprid can interfere on the soybean plant defence system by proteinase inhibitor activity. Newly emerged E. heros adults (< 72 h) were exposed to distilled water (control) or imidacloprid dried residuals for 48h. After that, one couple per plant was released in field cages with fourteen plants at pod filling (Rs-Rs). E. heros population was quantified at 15, 22, 30 and 45 days after infestation. Yield and seed quality were assessed at harvest (Rg). In order to study plant defence system a couple of stink bugs per plant or per pods was released in small cages, where they remained for seven days in a greenhouse. E. heros population was higher when stink bugs were previously exposed to imidacloprid than the control (distilled water). Infested soybean plants by E. heros exposed to imidacloprid had significant reduction 1n yield and lower quality seeds. Moreover, we found out E. heros can interfere soybean plant defence system. Therefore, our results showed that imidacloprid sublethal exposure may increase E. heros population and consequently reduce yield and seeds quality. In addition, this pest can likely change soybean seeds defence system.